2018
DOI: 10.1108/lm-04-2017-0038
|View full text |Cite
|
Sign up to set email alerts
|

Access to electronic and print information resources by people with visual impairments in university libraries

Abstract: Purpose The purpose of this paper is to discuss the implication of copyright on access to electronic and print information resources by people with visual impairments in university libraries. The paper examines the extent to which electronic and print information resources in university libraries are accessible to people with visual impairments; the extent to which existing national/international copyright laws facilitate or hamper access to electronic and print information resources by people with visual impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
1
7
0
1
Order By: Relevance
“…), and the quality of the relationship with the entity that created the product or service (what expectations does it create for subsequent interactions? ).” Services to the differently abled (Cassner et al , 2011), would reflect how they are handled by the libraries – for example, on the library website, the lived experiences of the differently abled (Majinge and Mutula, 2018; Mutula and Majinge, 2016), which is quite vital for addressing inequality scored only 38%. Evidently, dealing with inequality in information access and services is a major ethical issue and a challenge to African libraries, now and in the future.How do the academic libraries respond to the changing environment?…”
Section: Resultsmentioning
confidence: 99%
“…), and the quality of the relationship with the entity that created the product or service (what expectations does it create for subsequent interactions? ).” Services to the differently abled (Cassner et al , 2011), would reflect how they are handled by the libraries – for example, on the library website, the lived experiences of the differently abled (Majinge and Mutula, 2018; Mutula and Majinge, 2016), which is quite vital for addressing inequality scored only 38%. Evidently, dealing with inequality in information access and services is a major ethical issue and a challenge to African libraries, now and in the future.How do the academic libraries respond to the changing environment?…”
Section: Resultsmentioning
confidence: 99%
“…To understand the capillarity of the research on the 2030 Agenda, a first step is to take a look to systematic reviews and bibliometric analyses in the topic. In our research, we have identified 27 reviews so far, where the authors focus on studies of the implementation and the achievement of the SDGs (Barrantes Briceño and Almada Santos, 2019; Guha and Chakrabarti, 2019; Gusmão Caiado et al, 2018; Hristov and Chirico, 2019; Khan et al, 2019; Maroyi, 2018; Merino‐Saum et al, 2018; Omer and Noguchi, 2020; Schiappacasse and Müller, 2018; Zhang et al, 2019), on specific topics and collectives within the Agenda (Baum et al, 2016; Del Pino et al, 2019; Giné‐Garriga et al, 2017; Hartmann et al, 2016; Majinge and Mutula, 2018; Mathez‐Stiefel et al, 2017; Matilla et al, 2018; Simcock and Wittich, 2019; Swamy et al, 2018), on traditional fields of knowledge, now reconsidered in the light of the 2030 Agenda (Elfert, 2019; Rodrigues and Franco, 2019; Storey et al, 2017), and even on contributions to the field of knowledge from researchers in specific regions or countries (Körfgen et al, 2018; Staszkiewicz, 2019).…”
Section: The 2030 Agenda For Sustainable Developmentmentioning
confidence: 99%
“…The relevant literature identified several impediments that could make it difficult for students with visual impairments to access information in print and electronic resources. Majinge and Mutula, (2018) enumerated some impediments, such as: a lack of alternative document format that could be compatible with adaptive tools or assistive technology; inflexible copyright and licensing terms and conditions that require prior permissions of publishers and owners to transcribe content from textual to Braille format; design and layout of the library system features that are not user-friendly; and building designs that are not suitable for students with visual impairments. …”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, the overwhelming advent of the web-based applications into various educational settings has revolutionised the way of the course design and online delivery significantly and empowered academic libraries to make access to academic information quite easily to the students. Therefore, the academic networked libraries could help their users in using information in a knowledge base (Majinge and Mutula, 2018).…”
Section: Introductionmentioning
confidence: 99%